The Effect of Brand Image and Price Perception on Customer Satisfaction on Citilink Airlines at Juanda International Airport Surabaya - Affifah Dhiyaa Mahdianah; Arif Fakhrudin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The Central Statistics Agency (BPS) noted that the number of airplane passengers was 2.38 million people, an increase of 47.8% compared to the previous month. An increase in the number of passengers occurred at one of the main airports, namely Juanda Surabaya by 46%. The services provided by Citilink airline companies and price perceptions will affect the image in the future so that the airline must improve this to get Citilink airline user satisfaction. This study aims to determine the effect of Brand Image and Price Perception on Customer Satisfaction on Citilink Airlines at Juanda International Airport, Surabaya. Data analysis and hypothesis testing were carried out using multiple linear regression analysis through IBM SPSS Statistics 22. The results of this study indicate H1 is Ho is rejected and Ha is accepted, which means brand image has a positive and significant effect on customer satisfaction with a significant value of the brand image variable of 0.017 0 ,05. H2 is Ho is rejected and Ha is accepted, which means that price perception has a positive and significant effect on customer satisfaction with a significant value of the customer satisfaction variable of 0.006 0.05. H3 is Ho rejected and Ha accepted, which means brand image and price perception have a positive and significant effect on customer satisfaction with a significant value on the F test of 0.000 0.05. The result of the value of R Square (R2) is 35.8%.